Evaluation of Sodium Hypochlorite Irrigant, Bingpeng Irrigant, and Fufang Bingpeng Irrigant as Endodontic Irrigants During Passive Ultrasonic Irrigation - Shi, Yan; Deng, Zhipeng; Yang, Yulu; Cui, Lanyue; Chen, Tingtao; Hu, Mingjing; Xie, Lei; Yang, Jian (Frontiers in Cellular and Infection Microbiology, 2019)
The increased antibiotic resistant strains and side effects caused by synthetic drugs make it is a necessary to look for herbal alternatives. In the present study, the antimicrobial test, cell cytotoxicity test, cleaning test, q-PCR and high-throughput sequencing analyses were used to evaluate the potential of Fufang Bingpeng irrigant as root canal irrigant. Our in vitro results indicated that Fufang Bingpeng irrigant made a low minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for P. gingivalis ATCC 33277 (6.25% vs. 12.5%), P. intermedius ATCC 25611(6.25% vs. 6.25%), F. nucleatum ATCC 25286 (6.25% vs. 6.25%), E. faecalis ATCC 19433 (25% vs. 25%) and B. fragilis ATCC 25285 (12.5% vs. 12.5%), and could effectively remove the remaining debris and open dentinal tubules in root canals compared with NaCl irrigant (p<0.05). Moreover, Fufang Bingpeng irrigant also showed a low cytotoxicity on L929 cells compared with NaClO irrigant. In vivo results indicated only 1/104.95 bacteria remained in root canal using Fufang Bingpeng irrigant, and had better sustained the microbial diversity. Therefore, Fufang Bingpeng irrigant might be used as a potential root canal irrigant in clinic.